FYP student selection and examiner allocation system improvement part 2 - Wee, Teck Zong (Nanyang Technological University, 2021)
As Final Year Project (FYP) is a compulsory project as part of every student in the School of Computer Science and Engineering, Nanyang Technological University. A supervisor will oversee the projects for the period of over one year. The FYP will then be assessed and evaluated by not only the supervisor but also an examiner. Allocation of examiners to all the projects is one of the features of this FYP Examiner Allocation System (FEAS) project. The initial FEAS was designed and established in 2007 by a group of final year students who aimed to resolve the challenges faced by the FEA coordinator where manually assigning duties to faculty staffs and planning of the presenting schedule is tedious and not productive. Through the years, new innovative improvements were suggested and implemented to update the old and outdated system. After examining the system and discussing with the team, change request and new features were brought up. Better performance, security, and scalability were part of the enhancements mentioned, allowing the users to better serve its needs to the FEA coordinator. The Student Selection System (SSS) aims to ease the manual work of allocating students with their preferred choices of FYP. The current system was built and deployed once and never has much improvement for the past years, therefore, minor bugs could be fix and some improvements can be made to ensure that the SSS would function with better performance.